Sistem Kendali Kecepatan Robot Beroda Pada Jalan Menanjak dan Menurun Menggunakan Metode Proportional Integral Derivative - Muhammad Hanif Haikal; Dahnial Syauqy; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Abstract The development of the world of robotics is increasingly rapid, there is a human urge for all problems that arise around it so that it can be resolved quickly and efficiently. These problems are human limitation in processing control and a very long time, so that the more advanced the new technological era is, the more it is founds. For example in controlling speed on wheeled robots in terms of helping humans. The speed control system will be researched and applied to the skidsteering wheeled robot. This robot is equipped with an optocoupler sensor, Arduino UNO microcontroller and Motor Driver Shield L293D. this research method used is the Proportional Integral Derivative (PID). The access used is in the form of uphill and downhill roads on the slope of 10°, 15°,20° with the distance about 2m. From the simulation, the results are able to provide good control system performance criteria which can be seen from the comparison of the controller without using the PID controller and by using the PID control. PID contorl paramaters used to control DC motors are able to provide the most ideal control respone, with values of Kp = 0.2, Ki = 0.12 and Kd = 0.01. And when the robot run in the incline and descent area with an angle of 10°, 15°,20°, it has experienced a significant decrease in speed